2002
DOI: 10.3201/eid0812.020111
|View full text |Cite
|
Sign up to set email alerts
|

Human Pathogens in Body and Head Lice

Abstract: Using polymerase chain reaction and sequencing, we investigated the prevalence of Rickettsia prowazekii, Bartonella quintana, and Borrelia recurrentis in 841 body lice collected from various countries. We detected R. prowazekii in body lice from Burundi in 1997 and in lice from Burundi and Rwanda in 2001; B. quintana infections of body lice were widespread. We did not detect B. recurrentis in any lice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 15 publications
2
89
2
2
Order By: Relevance
“…Here, we find that there are more B. quintana in body lice than head lice. This finding could probably be explained through the role played by 30 These differences could be explained by the living conditions in jail in Rwanda and probably, the sample size in this study in Burundi. We have confirmed the presence of B. quintana in body lice in Rwanda and Burundi.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here, we find that there are more B. quintana in body lice than head lice. This finding could probably be explained through the role played by 30 These differences could be explained by the living conditions in jail in Rwanda and probably, the sample size in this study in Burundi. We have confirmed the presence of B. quintana in body lice in Rwanda and Burundi.…”
Section: Discussionmentioning
confidence: 92%
“…We have confirmed the presence of B. quintana in body lice in Rwanda and Burundi. 30 B. quintana has also been detected in body lice from homeless people in Zimbabwe (16.7%, 2/12). 30 This bacterium has not been found in body lice in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemic typhus is a louse-borne disease caused by Rickettsia prowazekii and endemic typhus caused by Rickettsia typhi is transmitted by fleas (Gunther, 1935;Weissmann, 2005). Epidemic typhus transmitted to humans through the body louse primarily occurs in areas of over population and people with lower socioeconomic condition (Fournier et al, 2002) which favors infestation of the vectors (Azad, 1998). Fever, nausea, muscle pain, and headaches are among the symptoms of epidemic typhus disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no strong evidence that head lice are vectors of this organism between human hosts. Moreover, Fournier et al 22 tested 143 head lice from schoolchildren from 8 countries and found no B quintana. We have detected B quintana in head lice from persons without a known concurrent body louse infestation.…”
Section: Discussionmentioning
confidence: 99%